Analisis Rancangan Strategi Pengembangan STIE Nobel Indonesia Menggunakan Balanced Scorecard - Mutiarini Mubyl; Muhammad Hidayat; Deddy Rahwandi (SEIKO : Journal of Management & Business, 2021)
Abstract This study aims to determine the analysis of the STIE Nobel Indonesia’s development strategy design using a balanced scorecard from the perspective of finance, customers, internal business processes, and learning and growth. The research design used was qualitative, involving 17 people of resource persons using a purposive sampling as a sampling technique and conducted at the STIE Nobel Indonesia Makassar campus, from December 2020 to March 2021. The data analysis method included triangulation from interviews, observations, and secondary / supporting data in the form of the STIE Nobel Indonesia Strategic Plan 2020-2024, and 9 Accreditation Criteria from BAN-PT. This study produced several development strategies designs from a financial perspective as many as 2 strategic targets with 2 strategic initiatives. From the customer's perspective there are 5 strategic objectives with 17 strategic initiatives. The internal business process perspective contains 11 strategic objectives with 42 strategic initiatives. Meanwhile, the learning and growth perspective has 5 strategic targets with 26 strategic initiatives. Keywords : development strategy, balanced scorecard